2017
DOI: 10.1016/j.jvs.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for stent graft-induced new entry after thoracic endovascular aortic repair for Stanford type B aortic dissection

Abstract: Distal oversizing of the stent graft was an independent predictor of the development of SINE. Appropriate size selection of stent graft without distal oversizing might reduce the risk of late SINE events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 24 publications
2
66
1
Order By: Relevance
“…Our previous study indicated that excessive oversizing was potential risk factor of reintervention . It was conceivable that too big oversizing would affect the vascular remodeling of postoperative aorta, resulting in more adverse events such as retrograde type A dissection, stent graft‐induced new entry and distal redissection . Therefore, the oversizing of stent graft for AAD should be recommended and restricted less than 10%, even nearly zero.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that excessive oversizing was potential risk factor of reintervention . It was conceivable that too big oversizing would affect the vascular remodeling of postoperative aorta, resulting in more adverse events such as retrograde type A dissection, stent graft‐induced new entry and distal redissection . Therefore, the oversizing of stent graft for AAD should be recommended and restricted less than 10%, even nearly zero.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting the appropriate size of SG in this pathology is important. An oversized SG might result in formation of a new tear around the edge of the SG,4, 5, 6 and a smaller size of SG can result in type Ia or Ib leakage with treatment failure. Currently, no consensus has been reached as how to decide on the size of an SG in AAD.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations increasing numbers of reports have demonstrated the beneficial effects of stent graft (SG) use in dissected descending aortic lesions 2, 3. However, devastating complications, such as retrograde type A dissection or formation of a new tear around the edge of an SG, have also been reported 4, 5, 6. One of the main factors involved in such disastrous complications is the use of an oversized SG for this pathology 6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive distal oversizing has been reported to be an independent predictor of SINE events, which usually require reintervention. It is believed that SINE events occur because of the fragility of the dissected intimal membrane in acute dissection as opposed to chronic dissection [39,40], although SINE events have been reported to be more common in chronic dissection [41]. However, a 2016 study of type B dissection cases reported that a distal-first rather than proximal-first deployment approach resulted in significantly fewer SINE events [42].…”
Section: Introductionmentioning
confidence: 99%